2012
DOI: 10.1002/mabi.201200295
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Preparation and pH‐Tunable Self‐Aggregation of Amphoteric Aliphatic Polycarbonates Bearing Plenty of Amine and Carboxyl Groups

Abstract: This paper reports a novel amphoteric aliphatic polycarbonate bearing both amine and carboxyl groups. In the absence of protection-deprotection chemistry, the multi-functionalized copolymer is synthesized by one-step enzymatic copolymerization. The influences of the reaction conditions including monomer feed ratio and polymerization time are explored. The simultaneous incorporation of amine and carboxyl functionalities provides the copolymer with a pH-tunable self-aggregation feature, leading to various aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Some reports suggest even quantitative removal of groups protecting carboxylic functionality [14]. Unfortunately, only few examples of single-step enzymatically catalyzed synthesis of polyacid via copolymerization of carboxylic-acid-functionalized carbonate were found in the literature [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggest even quantitative removal of groups protecting carboxylic functionality [14]. Unfortunately, only few examples of single-step enzymatically catalyzed synthesis of polyacid via copolymerization of carboxylic-acid-functionalized carbonate were found in the literature [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the form of an amphiphilic triblock copolymer ABA obtained using tertiary amine-functionalized APC diol as a telechelic initiator of enzymatic ROP of ε-caprolactone [98]. Furthermore, copolymer consisted of PEG and poly(tertiary amine-functionalized carbonate-co-ε-caprolactone) blocks [99], or amphoteric aliphatic copolycarbonates with amine and carboxyl groups in copolymer structure [100] were also reported.…”
Section: Polymers 2020 12 X For Peer Review 4 Of 31mentioning
confidence: 99%
“…70 and 90%, respectively. Using lipase, in a one-step reaction, the terpolymers of MTC-COOH with TMC and ADMC (6,14-dimethyl-1,3,9,11-tetraoxa-6,14-diaza-cyclohexadecane-2,10-dione) were also obtained [12]. Importantly, it was also found that coordination complexes such as zirconium IV acetylacetonate Zr(acac) 4 may be successfully used as initiators in the ROP of monomers with active carboxylic groups, such as MTC-COOH.…”
Section: Introductionmentioning
confidence: 99%